FRI0438 Psychometric properties of the german michigan hand questionnaire in patients with carpometacarpal osteoarthritis. (23rd January 2014) - Marks, M.; Herren, D.; Schindele, S.; Nelissen, R.; Vliet Vlieland, T.
Abstract : Background: The Michigan Hand Questionnaire (MHQ) is a self-administered questionnaire on hand function which, in contrast to other commonly used hand function questionnaires, yields results for each hand separately. The MHQ has been translated into German [1]. Its reliability and validity in patients with carpometacarpal osteoarthritis (CMC OA) have not been proved for either the English original or the German version, although it has already been used in several studies [2, 3]. Objectives: To investigate the internal consistency and convergent construct validity of the German MHQ for patients with CMC OA. Methods: Baseline data from consecutive patients included in a prospective, observational study on conservative and surgical treatment of CMC OA were used. All patients were asked to complete the MHQ, which consists of 37 items including six subscales: hand function, activities of daily living (ADL), pain, work performance, aesthetics, and satisfaction with hand function. The total score as well as the subscale scores are normalised and range from 0 to 100; higher scores indicate better performance, except for pain, where a higher score denotes more pain. Patients also filled in the Disabilities of Arm, Shoulder and Hand Questionnaire (DASH). For the MHQ, the percentage of missing items was calculated, as well as the percentage of patients obtaining the minimum or maximum score, in order to evaluate floor and ceiling effects. Internal consistency was measured by calculating Crohnbach's alpha. To investigate the convergent construct validity, correlations between the MHQ, its subscales and the DASH were calculated using Spearman's correlation coefficient. Results: 41 female and 10 male patients with a mean age of 64 years (SD ± 8.7) were included in the study. The median total score of the MHQ was 49 (range 23-88) for the affected hand and 65 (28-92) for the non-affected hand, with 0.03% missing items in total. No patient obtained either the minimum or the maximum total score. Internal consistency ranged from α =0.76 for the MHQ work subscale to α =0.89 for the ADL subscale. ADL (r=-0.69**), work (r=-0.55**) and pain (r=0.64**), as well as the total score (r=-0.62**), correlated well with the DASH, whereas satisfaction (r=-0.44**) and hand function (r= -0.28*) showed modest, yet statistically significant correlations (*=p≤0.05, **=p≤0.01). The aesthetics subscale did not correlate significantly with the DASH (r=-0.19). Conclusions: The German MHQ seems to be an internally consistent and valid questionnaire for measuring hand function in patients with CMC OA. Its responsiveness in this particular patient group needs to be determined in future research. References: K Knobloch, et al. Plast Reconstr Surg. 2011; 128: 39e-40e J Van Rijn, et al. J.Hand Surg.Am. 2010; 35: 572-9 NG Burke, et al. J Hand Surg Eur Vol. 2011; Epub 2011/09/15 Disclosure of Interest: None Declared